2017
DOI: 10.1016/j.jqsrt.2016.12.030
|View full text |Cite
|
Sign up to set email alerts
|

The applicability of physical optics in the millimetre and sub-millimetre spectral region. Part I: The ray tracing with diffraction on facets method

Abstract: Future satellite missions, from 2021 onwards, will obtain near-global measurements of cirrus at microwave and sub-millimetre frequencies. To realise the potential of these observations, fast and accurate light scattering methods are required to calculate scattered millimetre and sub-millimetre intensities from complex ice crystals. Here, the applicability of the ray tracing with diffraction on facets method (RTDF) in predicting the bulk scalar optical properties and phase functions of randomly oriented hexagon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…This potential inaccuracy must not be ignored, but should today be relatively small compared to all other uncertainties involved in full simulations and retrievals. For example, Baran et al (2017) reasoned in the same way and were also content with a 10 % accuracy. However, much higher discrepancies were found occasionally, particularly regarding backscattering.…”
Section: Discussionmentioning
confidence: 99%
“…This potential inaccuracy must not be ignored, but should today be relatively small compared to all other uncertainties involved in full simulations and retrievals. For example, Baran et al (2017) reasoned in the same way and were also content with a 10 % accuracy. However, much higher discrepancies were found occasionally, particularly regarding backscattering.…”
Section: Discussionmentioning
confidence: 99%
“…However, improvements to geometric optics methods have been shown to be accurate for x as small as 18, e.g. using methods such as ray tracing with diffraction on facets (RTDF; [46]). Hence it is possible that for the larger size parameters considered here, physical or geometric optics methods may be suitable approximations to apply.…”
Section: Convergence Of Dda Internal Field Results With Increasing N λmentioning
confidence: 99%
“…The bulk single-scattering properties of these two models are computed using the light-scattering methods described in Part I. In Part I, it was shown that the physical optics method was applicable in the microwave region down to size parameters of about 18, where the size parameter was defined as D/; this same definition of the size parameter is used in this paper [29]. The bridging between the electromagnetic and physical optics methods applied at size parameters smaller or greater than 18, respectively, was achieved using the ray tracing with diffraction on facets (RTDF) method developed by Ref.…”
Section: Introductionmentioning
confidence: 99%